Możliwości diagnostyczne modułu rogówkowego HRT II - Michalewska, Zofia; Michalewski, Janusz; Nawrocka, Zofia (Klinika Oczna / Acta Ophthalmologica Polonica, 2008)
Purpose: The aim of this paper is to present corneal layers of healthy individuals with a confocal laser scanning ophthalmoscope (Heidelberg Retina Tomograph/ Rostock Cornea Module). Material and methods: We analyzed 40 corneas of 20 healthy individuals and measured corneal thickness and thickness of corneal layers. We also describe cell characteristics of each layer. Results: In the outer endothelium 846 cells/mm2 were observed. In the medium endothelium 5000 cells/mm2 and in the inner endothelium about 9000 cells/mm2 were noted. 34 Langerhans cells/mm2 in the centre and 92 Langerhans cells/mm2 were present. The mean keratocyte nuclei count in the stroma was 355/mm2 . In the endothelium we noted a mean of 2960 cells/mm2 . Our data are similar to data obtained by histopathological findings. Conclusions: HRT II cornea module is a noninvasive, rapid and repeatable instrument that enables not only measurement of corneal thickness but also the exact cell count. It can be an important tool in diagnosis and evaluation of treatment of various corneal diseases.